PENGARUH INSENTIF PAJAK DAN DIGITALISASI PELAYANAN PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK BADAN DI KPP PRATAMA KEDIRI - Aditya Wahyu Jatmika; Puspita, Ayu Fury (Reviu Akuntansi, Keuangan, dan Sistem Informasi, 2024)
The declining tax ratio indicates decreased taxpayer compliance in Indonesia especially in 2019 and 2020, including that in KPP Pratama Kediri where the number of taxpayers has increased. As such, to increase taxpayer compliance, in response to taxpayer dissatisfaction, the government improve the service through tax service digitalization, and tax incentives during the Covid-19 pandemic. This study aims to determine and analyze the effect of tax incentives and tax service digitalization on corporate taxpayer compliance of KPP Pratama Kediri. This study employs a quantitative method with hypothesis testing, and the data are collected through questionnaires. The samples include 349 respondents of corporate taxpayers registered in KPP Pratama Kediri selected through the purposive sampling method. The results of this study indicated that tax incentives and tax service digitalization had a positive and significant effect on corporate taxpayer compliance.